Analysis of the intent to purchase travel on the web - Gemar,German (2019)
The role of the Internet in the development of global markets offers a valuable object of study. This is especially true for tourism, both because of its contribution to the Spanish economy and because its intangible nature makes the Internet the most effective dist ribution channel for it. To help companies differentiate their websites, this work proposed a model of purchase intention, which includes the determinants of that intention. Cluster analysis was performed on a representative sample to sort potential and current consumers of online travel into groups based on their perceptions of the factors of the model. While young consumers see purchasing tourism - related services on the Internet as easy and cost-effective, contrary results are obtained for the elderly. However, the perceived risk is relevant for most individuals. In order to optimise the benefits of e - commerce, companies must build strategies that meet the expectations of each type of client.